2010
DOI: 10.1111/j.1477-2574.2009.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in patients with unresectable hepatocellular carcinoma undergoing chemoembolization with doxorubicin drug-eluting beads: a preliminary study

Abstract: Child-Pugh class, Okuda staging, bilirubin > 2 mg/dl, albumin < 3 g/dl, MELD score, serum AFP, CLIP score, Milan criteria, ECOG PS and BCLC staging were found to be prognostic markers of survival after treatment with doxorubicin DEB TACE in patients with unresectable HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 25 publications
8
23
1
Order By: Relevance
“…reported 3‐year survival rates of 26% and 3%, respectively. The present study has confirmed that a reduction in serum AFP, 36 repetition of TACEs, 37,38 low MELD score, 39 the absence of diffuse disease 40,41 and small tumour size 42 are all associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 83%
“…reported 3‐year survival rates of 26% and 3%, respectively. The present study has confirmed that a reduction in serum AFP, 36 repetition of TACEs, 37,38 low MELD score, 39 the absence of diffuse disease 40,41 and small tumour size 42 are all associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 83%
“…CLIP score accounts for both tumor characteristics and liver function relevant to prognostic assessment for patients with HCC. As described in previous studies [30], [31], the present study showed that CLIP score before TACE was an independent factors associated with overall survival after TACE. The present study showed that the predictive ability of 1-year mortality by CLIP score was better than that by npRQ ratio.…”
Section: Discussionsupporting
confidence: 88%
“…The overall survival reported in this study reflects this inclusion of more patients with baseline poorer liver function. In other studies similar to this one with higher rates of advanced cirrhosis (34–63%) and survival rates range from 6–21 months 19–21 . In Dhanasekaran et al .…”
Section: Discussionsupporting
confidence: 62%
“…In Dhanasekaran et al . ‘s work on prognostic factors in doxorubicin‐bead TACE therapy in HCC, they found 7 out of 10 reported prognostic factors were associated with liver function rather than tumour stage 20 …”
Section: Discussionmentioning
confidence: 99%